2006
DOI: 10.1007/s11240-006-9126-y
|View full text |Cite
|
Sign up to set email alerts
|

Dose-, time-, and tissue-dependent effects of 5-bromo-2′ -deoxyuridine on the in-vitro organogenesis of Arabidopsis thaliana

Abstract: Vigorous organogenesis can be induced from hypocotyl and root explants of Arabidopsis thaliana using a two-step culture procedure consisting of preculture on callusinducing medium (CIM) and subsequent culture on shoot-inducing medium (SIM) or root-inducing medium (RIM). With this culture system, we examined the influence of 5-bromo-2¢-deoxyuridine (BrdU), a thymidine (dT) analogue, on plant organogenesis in vitro. Treatment with BrdU during SIM or RIM culture had negative effects on shoot and root redifferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The use of plant growth regulators is of fundamental importance for controlling the organogenic response of each plant tissue/organ under in vitro conditions (Che et al, 2002 andSugiyama &Imamura, 2006). Studies have shown that 2,4-D is one of the most effective auxins for induction and growth of callus (Lee et al, 2004 andBurbulis et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The use of plant growth regulators is of fundamental importance for controlling the organogenic response of each plant tissue/organ under in vitro conditions (Che et al, 2002 andSugiyama &Imamura, 2006). Studies have shown that 2,4-D is one of the most effective auxins for induction and growth of callus (Lee et al, 2004 andBurbulis et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The inducing rate of stem tip was more than 80% in the medium with the concentrations of 0.2 mg/l and 0.5 mg/l 2.4-D (Table 1). The use of plant growth regulators is of fundamental importance in directing the organogenic response of any plant tissue or organ under in vitro conditions (Sugiyama and Imamura, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…This might reflect the difference of cell state between hypocotyls and roots. Preculture with bromodeoxyuridine, an analog of thymidine, in CIM can inhibit shoot regeneration from hypocotyl explants but not from roots on SIM (Sugiyama and Imamura 2006). The methylation of DNA occurring in root explants might be irreversible and not be recovered by AzaC.…”
Section: Discussionmentioning
confidence: 99%